Method for cleaning heavy metal gypsum residues

Through the three-stage roasting process of heavy metal gypsum slag as solid ion exchanger and the low-acid leaching process, the problem of low efficiency in the resource treatment of heavy metal gypsum slag is solved, and efficient extraction and toxicity of valuable metals in high ferrosilicon cobalt slag is achieved. Depth removal of elements is suitable for industrial applications.

CN119120908APending Publication Date: 2024-12-13CENT SOUTH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411271540.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, the resource treatment efficiency of heavy metal gypsum slag is low, making it difficult to achieve efficient extraction of valuable components and deep removal of toxic elements.

Method used

Heavy metal gypsum slag is used as solid ion exchanger, and the deconstruction of high ferrosilicon cobalt slag and the extraction of valuable metals are achieved through a three-stage roasting process, and combined with a low acid leaching process, it deeply removes harmful elements such as F, Cl, As and other harmful elements.

Benefits of technology

It has achieved deep removal of poisoned elements in heavy metal gypsum slag and efficient utilization of valuable components, improved the leaching rate of iron and cobalt, simple process and low energy consumption, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120908A_ABST
    Figure CN119120908A_ABST
Patent Text Reader

Abstract

The invention discloses a method for cleaning heavy metal gypsum residues, and belongs to the technical field of solid waste resource utilization. The method comprises the following steps: grinding and mixing heavy metal gypsum slag, high-silicon iron-cobalt slag and a carbonaceous reducing agent, and then sequentially carrying out three-stage roasting and first-stage roasting to volatilize and remove harmful components including F, Cl and As; calcium sulfate is decomposed and converted into calcium oxide and sulfur dioxide through second-stage roasting; phase reconstruction of the high-silicon iron-cobalt slag is achieved through three-section roasting, and a roasted product containing Fe2O3, Fe3O4, CoO, Co3O4 and CaSiO3 is obtained; and the roasted product is subjected to acid leaching, and iron-cobalt leaching liquid is obtained. According to the method, cooperative treatment of the heavy metal gypsum slag and the high-silicon iron-cobalt slag can be achieved, and the technical problems that the content of toxic elements in the heavy metal gypsum slag is high, environmental pollution is serious, and Fe2SiO4 and Co2SiO4 structures in the high-silicon iron-cobalt slag are difficult to damage are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for treating heavy metal gypsum slag, and in particular to a method for cleanly treating high-silicon iron-cobalt slag by using heavy metal gypsum slag as a solid ion exchanger to realize resource utilization, belonging to the technical field of solid waste resource utilization. Background Art

[0002] The annual stockpile of heavy metal gypsum slag is increasing day by day. Its chemical composition is complex and contains many kinds of toxic and harmful elements. Generally, this type of hazardous solid waste is treated and utilized in a green way through reduction treatment, resource treatment and harmless treatment. Among them, reduction treatment mainly relies on enterprises to continuously optimize production processes and develop new technologies to minimize the amount of heavy metal gypsum slag produced at the source of waste acid disposal and achieve gypsum slag reduction; resource treatment of gypsum slag gives priority to the recovery of valuable elements contained in heavy metal gypsum slag, such as the recovery and utilization of metals such as calcium, zinc, copper, lead and nickel, so as to reduce the pressure of lack of primary mineral resources, or use it to produce new building materials, etc., to solve the environmental pollution caused by heavy metal gypsum slag; harmless treatment of heavy metal gypsum slag is mainly solidification / stabilization treatment, that is, to wrap hazardous waste with stable or inert materials to stabilize its state and prevent the migration and diffusion of toxic elements in the environment. Such technology can effectively treat toxic solid waste, but it cannot guarantee that it will not have an impact on human health and the environment in the future.

[0003] The prior art has disclosed a technology for treating gypsum slag. For example, Chinese patent CN110983029A proposes a method for co-sulfurization roasting of lead-zinc smelting slag and gypsum slag. The lead-zinc smelting slag, gypsum slag, and a carbonaceous reducing agent are mixed and reduced and sulfided and roasted. The gypsum slag is used as a sulfiding agent to convert the heavy metals such as lead and zinc in the lead-zinc smelting slag into metal sulfides that are easy to float and separate. The calcium in the gypsum slag reacts with the iron and silicon compounds in the lead-zinc smelting slag to form calcium ferrite and calcium silicate compounds. The arsenic in the gypsum slag is volatilized and enriched in the smoke and recovered. The method has the following problems: low flotation separation efficiency, the flotation product still needs to be processed by pyrometallurgical or hydrometallurgical processes, the flotation has high requirements on the particle size of the sulfidation product, and the overall process is long. This method cannot fundamentally solve the resource utilization of heavy metal gypsum slag. Chinese patent CN114477818A discloses a method for achieving efficient detoxification of heavy metal gypsum slag at normal temperature and pressure. The gypsum slag is wetted by an acidic solution, and the phase change of gypsum to anhydrous gypsum and the separation and extraction of heavy metals are simultaneously achieved. The solid product is anhydrous gypsum, and the detoxification rate can be as high as 90% to 100%. This method only studies the removal of As in heavy metal gypsum slag, and other metal elements such as Zn and Fe are not mentioned. Summary of the invention

[0004] In view of the technical problems of low separation efficiency of valuable components and incomplete resource treatment in the process of resource treatment of heavy metal gypsum slag in the prior art, the purpose of the present invention is to provide a method for clean treatment of heavy metal gypsum slag. The method uses the idea of ​​"treating waste with waste" to use the high content of calcium sulfate in the heavy metal gypsum slag as a solid ion exchanger, and achieves deep removal of poisonous elements F, Cl, and As during the roasting process, and complete deconstruction of high silicon iron cobalt slag to obtain roasting products Fe2O3, Fe3O4, CoO, Co3O4 and CaSiO3; then, the iron-cobalt leaching solution is obtained by warm acid leaching. The method achieves the deep removal of poisonous elements and the comprehensive utilization of valuable components in heavy metal gypsum slag, and at the same time, it also achieves the purpose of in-situ deconstruction of high silicon iron cobalt slag and efficient extraction of valuable metals.

[0005] In order to achieve the above technical objectives, the present invention provides a method for cleaning heavy metal gypsum slag, the method comprising grinding and mixing heavy metal gypsum slag, high silicon iron cobalt slag and a carbonaceous reducing agent to obtain a mixed powder; the mixed powder is sequentially subjected to three-stage roasting, wherein the first stage of roasting volatilizes and removes harmful components including F, Cl and As; the second stage of roasting decomposes calcium sulfate and converts it into calcium oxide and sulfur dioxide; the third stage of roasting realizes phase reconstruction of the high silicon iron cobalt slag to obtain a roasting product including Fe2O3, Fe3O4, CoO, Co3O4 and CaSiO3; the roasting product is subjected to acid leaching to obtain an iron-cobalt leaching solution.

[0006] The key to the method for cleaning heavy metal gypsum slag provided by the present invention is to use heavy metal gypsum slag as a solid ion exchanger to achieve the physical phase reconstruction of Fe2SiO4 and Co2SiO4 in high silicon iron cobalt slag, so that the minerals such as Fe2SiO4 and Co2SiO4 that are difficult to leach are converted into phases containing Fe2O3, Fe3O4, CoO, Co3O4, etc. that are easy to leach with low acid and low temperature. However, the main component of heavy metal gypsum slag is calcium sulfate, which does not contain active calcium components and cannot be directly used as a solid ion exchanger to achieve the physical phase reconstruction of Fe2SiO4 and Co2SiO4. At the same time, it also contains a large number of harmful components. Therefore, heavy metal gypsum slag must be combined with special roasting treatment to fully exert its function as a solid ion exchanger. The roasting treatment mainly includes a three-stage roasting process. First, harmful components are removed by low-temperature roasting, then medium-temperature roasting is used to decompose the calcium sulfate component and convert it into a highly active calcium component. Finally, high-temperature roasting is used to utilize the active calcium component to undergo a high-temperature solid-phase reaction with minerals such as Fe2SiO4 and Co2SiO4 to achieve the reconstruction of minerals such as Fe2SiO4 and Co2SiO4, and convert them into phases such as Fe2O3, Fe3O4, CoO, and Co3O4, which can be leached using low temperature and low acid. In the first stage of roasting, harmful components such as F, Cl and As enter the flue gas and can be directly recovered from the flue gas. In the second stage of roasting, calcium sulfate is mainly decomposed. Under the action of carbonaceous reducing agent, the main reactions are as follows: CaSO4+C→CaS+CO2(g)(1); CaSO4+CaS→CaO+SO2(g)(2); In the third stage of roasting, mineral reconstruction such as Fe2SiO4 and Co2SiO4 is mainly achieved. The main reactions are as follows: CaO→Ca 1-x O+xCa(II)(3);yCa(II)+Fe2SiO4→[(Fe (2-y) Ca y )SiO4]yFe(II)(4);yCa(II)+Co2SiO4→[(Co (2-y) Ca y )SiO4]yCo(II)(5);[(Fe (2-y) Ca y )SiO4]yFe(II)→(Fe (2-y) Ca y )Si (1-x) O z +yFe(II)+xSiO2(6);[(Co (2-y) Ca y )SiO4]yCo(II)→(Co (2-y) Ca y )Si (1-x) O z +yCo(II)+xSiO2(7);yFe(II)+Ca1-x O→(Ca (1-x) Fe(II) x )O(8);yCo(II)+Ca 1-x O→(Ca (1-x) Co(II) x )O(9);CaO+SiO2→CaSiO3(10). The final calcined products such as Fe2O3, Fe3O4, CoO, Co3O4, etc. can be obtained by low temperature acid leaching.

[0007] The innovative points of the technical solution of the present invention are as follows: ① Using the innovative idea of ​​"using waste to treat waste", the calcium sulfate in the heavy metal gypsum slag is first decomposed into calcium oxide during the roasting process, and then dissociated into Ca(II) and calcium-deficient Ca at high temperature. 1-x O. The Fe(II) ions at the M2 site of Fe2SiO4 are replaced by the released Ca(II) ions to form [(Fe (2-y) Ca y )SiO4] y Fe(II); subsequently, the substituted Fe(II) occupies Ca 1-y O, forming a Ca vacancy (Ca (1-x) Fe(II) x )O; disproportionation of Fe(II) and the combination of CaO and SiO2 separated from Fe2SiO4 generate the final products Fe2O3, Fe3O4 and CaSiO3. Similarly, the Co(II) ions at the M2 site of Co2SiO4 are replaced by the released Ca(II) ions to form [(Co (2-y) Ca y )SiO4] y Co(II); subsequently, the substituted Co(II) occupies Ca 1-y O, forming a Ca vacancy (Ca (1-x) Co(II) x )O. Co(II) and CaO react with SiO2 separated from Co2SiO4 to generate the final products Co3O4 and CaSiO3. ② By controlling different roasting temperatures, the selective removal of poisonous elements, the selective decomposition of calcium sulfate and the in-situ decomposition of Fe2SiO4 and Co2SiO4 in high silicon iron cobalt slag are achieved; ③ In the second stage roasting process, the sulfur dioxide gas generated during the roasting process is passed into a reaction vessel filled with hydrogen peroxide to convert sulfur dioxide into sulfuric acid for the subsequent leaching of iron and cobalt elements.

[0008] As a preferred solution, the mass ratio of heavy metal gypsum slag and high silicon iron cobalt slag in the mixed powder is m (重金属石膏污泥) :m (高硅铁钴渣)=1~3. The main component of heavy metal gypsum sludge is calcium sulfate, while the main components of high silicon iron cobalt slag are Fe2SiO4 and Co2SiO4. The ratio of heavy metal gypsum sludge to high silicon iron cobalt slag can be determined according to the ratio of calcium sulfate to Fe2SiO4 and Co2SiO4 contained therein. The minimum amount of heavy metal gypsum sludge should ensure that all the silicon in Fe2SiO4 and Co2SiO4 in high silicon iron cobalt slag is combined with calcium and converted into calcium silicate components. However, excessive amount of heavy metal gypsum sludge will cause part of the iron cobalt oxide to be converted into calcium salt. The mass ratio of heavy metal gypsum sludge to high silicon iron cobalt slag is further preferably m (heavy metal gypsum sludge): m (high silicon iron cobalt slag) = 1.5~2.

[0009] As a preferred solution, the mass content of CaSO4 in the heavy metal gypsum slag is 65-85%. The remaining components and their mass contents are: 1%-3% of fluorine-containing compounds, no more than 2% of chlorine-containing compounds, and 1-5% of As compounds.

[0010] As a preferred solution, the mass content of Fe2SiO4 in the high silicon iron cobalt slag is 60-80wt%, and the mass content of Co2SiO4 is 10-15%. It should be noted that the Fe2SiO4 and Co2SiO4 in the high silicon iron cobalt slag are iron olivine structures, and usually need to be in a high concentration of acid solution to destroy their structure. For example, Chinese patent CN 115491508 A proposes that the valuable elements in iron olivine can only be dissolved under the condition of sulfuric acid concentration of 90-200g / L, which has the disadvantage of high acid dosage and complicated subsequent waste liquid treatment. Therefore, the present invention uses heavy metal gypsum slag as a solid ion exchanger to achieve complete decomposition of Fe2SiO4 and Co2SiO4 during the co-roasting process, which is of great significance for extracting valuable elements from high silicon iron cobalt slag.

[0011] As a preferred solution, the amount of the carbonaceous reducing agent is 5% to 20% of the mass of the heavy metal gypsum slag and the high silicon iron cobalt slag. When the mass proportion of the carbonaceous reducing agent is too high, a large amount of metal sulfides will be generated, which is not conducive to the subsequent high-temperature solid phase reaction. If the mass proportion of the carbonaceous reducing agent is too low, it will lead to the overflow of sulfur dioxide gas. The carbonaceous reducing agent is, for example, carbon powder. The amount of the carbonaceous reducing agent is further preferably 5% to 15% of the mass of the heavy metal gypsum slag and the high silicon iron cobalt slag.

[0012] As a preferred solution, the conditions for the one-stage roasting are: roasting under a protective atmosphere, a roasting temperature of 500-800°C, and a roasting time of 30-120 min. The one-stage roasting is mainly for detoxification of gypsum, and the volatilization and removal of harmful components including F, Cl and As at low temperature. The protective atmosphere is a flowing inert gas or nitrogen. The one-stage roasting temperature is further preferably 500-700°C; the roasting time is further preferably 60-90 min. If the roasting temperature is too high, part of the calcium sulfate will decompose, which is not conducive to the centralized treatment of sulfur dioxide. If the roasting temperature is too low, the harmful components will not be completely removed, which is not conducive to subsequent reactions.

[0013] As a preferred solution, the conditions of the second stage roasting are: roasting under a protective atmosphere, the roasting temperature is 800-900°C, and the roasting time is 30-90 minutes. The second stage roasting is mainly to achieve high temperature pyrolysis of calcium sulfate to produce active Ca(II) and calcium-deficient Ca 1-x O is the main solid ion exchanger for the conversion of Fe2SiO4 and Co2SiO4. The protective atmosphere is a flowing inert gas or nitrogen. If the roasting temperature is too low, it will not be conducive to the full progress of reactions ① and ②, resulting in the inability to fully pyrolyze calcium sulfate; if the roasting temperature is too high, it will easily cause the carbon powder to react with Fe2SiO4 and Co2SiO4, so that the calcium sulfate cannot be fully decomposed. Similarly, if the roasting time is too short, the calcium sulfate cannot be fully pyrolyzed; if the roasting time is too long, the cost will be increased. The second-stage roasting temperature is further preferably 850-900°C; the roasting time is further preferably 60min-90min.

[0014] As a preferred solution, the conditions of the three-stage roasting are: roasting under a protective atmosphere, a roasting temperature of 900-1200°C, and a roasting time of 30min-180min. The three-stage roasting mainly utilizes the active calcium component to react with minerals such as Fe2SiO4 and Co2SiO4 at a high temperature solid phase to achieve the reconstruction of minerals such as Fe2SiO4 and Co2SiO4, and convert them into phases such as Fe2O3, Fe3O4, CoO, and Co3O4. The protective atmosphere is a flowing inert gas or nitrogen. If the roasting temperature is too low, it is not conducive to the full progress of reactions ③ to ⑩, resulting in the inability to fully decompose Fe2SiO4 and Co2SiO4; if the roasting temperature is too high, it will cause high energy consumption and increase costs. Similarly, if the roasting time is too short, Fe2SiO4 and Co2SiO4 cannot be fully decomposed; if the roasting time is too long, the cost will be increased. The three-stage calcination temperature is more preferably 900 to 1150° C., and the calcination time is more preferably 90 to 120 minutes.

[0015] As a preferred solution, the acid leaching conditions are: leaching temperature of 45-65°C, leaching time of 30-60 min, and acid concentration of 0.2-0.5 mol / L. As a more preferred solution, the acid is sulfuric acid. The leaching temperature is more preferably 55-65°C, the leaching time is more preferably 45-60 min, and the sulfuric acid concentration is more preferably 0.2-0.4 mol / L.

[0016] Compared with the prior art, the beneficial technical effects brought by the present invention are as follows:

[0017] 1) The present invention is the first to propose a co-roasting-low acid leaching process of heavy metal gypsum slag as a solid ion exchanger with high silicon iron cobalt slag, thereby realizing the clean utilization of heavy metal gypsum slag and high silicon iron cobalt slag.

[0018] 2) The present invention utilizes the in-situ characteristics of elements in heavy metal gypsum slag and fayalite slag, and achieves the selective removal of poisonous elements F, Cl, and As, the selective thermal decomposition of calcium sulfate, and the in-situ decomposition of Fe2SiO4 and Co2SiO4 by controlling the roasting temperature at different stages.

[0019] 3) The present invention realizes efficient leaching of iron and cobalt in high-silicon ferrocobalt slag through a low-acid leaching process.

[0020] 4) The present invention converts the sulfur dioxide generated during the second-stage roasting process into sulfuric acid for subsequent leaching.

[0021] 5) The process of the present invention is simple, has low energy consumption, and less pollution, and is conducive to industrial production.

[0022] In summary, the present invention proposes for the first time a "waste treatment with waste" treatment scheme for heavy metal gypsum slag and high silicon iron cobalt slag, and achieves a removal rate of more than 98% for the poisonous elements F, Cl, and As through a three-stage roasting-low acid leaching process, and directionally converts Fe2SiO4, Co2SiO4, and CaSO4 into Fe2O3, Fe3O4, CoO, Co3O4, and CaSiO3; finally, a low-temperature sulfuric acid leaching process is used to achieve a leaching rate of iron and cobalt of more than 99%, thereby solving the problem of green comprehensive utilization of heavy metal gypsum slag and high silicon iron cobalt slag, and realizing efficient leaching of valuable elements iron and cobalt. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a process flow chart for resource treatment of heavy metal gypsum slag and high silicon iron cobalt slag.

[0024] Figure 2 This is the XRD spectrum of the heavy metal gypsum slag in Example 1.

[0025] Figure 3This is the XRD spectrum of the high silicon iron cobalt slag of Example 1.

[0026] Figure 4 This is the XRD pattern of the final calcined product in Example 1. DETAILED DESCRIPTION

[0027] The present invention will be described below in conjunction with the embodiments. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. Unless otherwise specified, the relevant percentages refer to mass percentages.

[0028] Example 1

[0029] The raw material of heavy metal gypsum slag comes from a lead-zinc smelter of a new energy enterprise in Hunan, and the raw material of high silicon iron cobalt slag comes from a copper smelter in Africa. The Ca content of heavy metal gypsum slag is 35.14%, the S content is 23.24%, the O content is 39.12%, the F content is 0.9%, the Cl content is 0.35%, and the As content is 0.83%; the Fe content of high silicon iron cobalt slag is 35.48%, the Co content is 6.17%, the Si content is 18.14%, and the O content is 41.21%. XRD was used to characterize the main phases in heavy metal gypsum slag and high silicon iron cobalt slag, and the analysis results are as follows Figure 2 , Figure 3 As shown, according to Figure 2 and Figure 3 It can be concluded that the main component of heavy metal gypsum slag is calcium sulfate dihydrate, and the main component of olivine slag exists in the form of Fe2SiO4 and Co2SiO4.

[0030] according to Figure 1 The specific treatment process of heavy metal gypsum slag and high silicon iron cobalt slag includes the following steps:

[0031] S1. The heavy metal gypsum slag and high silicon iron cobalt slag to be treated are proportioned, and then carbon powder is added and ground evenly. Specifically, m (heavy metal gypsum slag): m (high silicon iron cobalt slag) = 2, and the amount of carbon powder is 10%.

[0032] S2. The ground mixture is subjected to a roasting treatment at a temperature of 700° C., nitrogen is an inert gas, the inert gas flow rate is 2 L / min, and the roasting time is 90 min to obtain a volatile product (a mixture of F, Cl, and As), wherein the volatility of F, Cl, and As reaches 98.11%, 98.35%, and 98.08%, respectively.

[0033] S3. The remaining calcination residue is subjected to a second-stage calcination at a calcination temperature of 900° C., nitrogen is used as the inert gas, the inert gas flow rate is 2 L / min, and the calcination time is 90 min, so that the calcium sulfate is fully decomposed.

[0034] S4, the decomposed calcined residue was calcined in three stages, the calcination temperature was 1150°C, the inert gas was nitrogen, the inert gas flow rate was 2L / min, the calcination time was 120min, Fe2SiO4 and Co2SiO4 were in situ decomposed, and the calcined product was obtained. The XRD spectrum of the product is shown in Figure 4 .

[0035] S5. The roasted product obtained in the third stage of roasting is subjected to low-temperature acid leaching, the leaching temperature is 65° C., the leaching time is 60 min, and the sulfuric acid concentration is 0.4 mol / L. The leaching rates of iron and cobalt in the final roasted product reach 99.12% and 99.34%, respectively.

[0036] Example 2

[0037] Example 1 was repeated, with the only difference being that m(heavy metal gypsum slag): m(high silicon iron cobalt slag) = 1.5 in S1, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt were 91.24% and 93.09% respectively after the roasted product was treated with low-temperature acid leaching, indicating that an appropriate increase in m(heavy metal gypsum slag) was beneficial to fully decompose Fe2SiO4 and Co2SiO4 in the high silicon iron cobalt slag during the co-roasting process, thereby improving the leaching rates of iron and cobalt during the low-temperature acid leaching process.

[0038] Example 3

[0039] Example 1 was repeated, with the only difference being that m(heavy metal gypsum slag): m(high silicon iron cobalt slag) = 2.2 in S1, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 99.17% and 99.35%, respectively, indicating that further increasing m(heavy metal gypsum slag) had little effect on promoting the decomposition of Fe2SiO4 and Co2SiO4 in high silicon iron cobalt slag. Therefore, the leaching rates of iron and cobalt in the low-temperature acid leaching process did not change much.

[0040] Example 4

[0041] Example 1 was repeated, except that the amount of carbon powder in S1 was 7%, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 93.11% and 94.21%, respectively, indicating that increasing the amount of carbon powder is beneficial to promoting the decomposition of calcium sulfate into calcium oxide, that is, promoting the occurrence of reaction (1) and reaction (2), thereby further promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high-silicon iron-cobalt slag during the co-roasting process, thereby improving the leaching rate of iron and cobalt in the low-temperature acid leaching process.

[0042] Example 5

[0043] Example 1 was repeated, except that the amount of carbon powder in S1 was 12%, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 99.13% and 99.25%, respectively, indicating that increasing the amount of carbon powder is beneficial to promoting the decomposition of calcium sulfate into calcium oxide, that is, promoting the occurrence of reaction (1) and reaction (2), thereby promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high-silicon iron-cobalt slag during the co-roasting process, thereby improving the leaching rates of iron and cobalt during the low-temperature acid leaching process.

[0044] Example 6

[0045] Example 1 was repeated, except that the calcination temperature in S2 was 650°C, and the other conditions remained unchanged. The results showed that the removal rates of the poisonous elements F, Cl, and As were 96.31%, 96.35%, and 95.98%, respectively. This shows that increasing the calcination temperature in the first stage is beneficial to the removal of F, Cl, and As.

[0046] Example 7

[0047] Example 1 was repeated, with the only difference being that the roasting temperature in S2 was 750°C, and the other conditions remained unchanged. The results showed that the removal rates of the poisonous elements F, Cl, and As were 98.21%, 98.38%, and 98.16%, respectively. This shows that increasing the roasting temperature in the first stage is beneficial to the removal of F, Cl, and As, but the change is not obvious. In addition, continuing to increase the temperature may be accompanied by the decomposition of calcium sulfate, thereby causing F, Cl, and As to mix with SO2 gas, which is not conducive to the subsequent separate recovery of sulfur dioxide. Therefore, the temperature for selectively removing F, Cl, and As in the first stage should not be too high.

[0048] Example 8

[0049] Example 1 was repeated, except that the calcination time in S2 was 70 min, and the other conditions remained unchanged. The results showed that the removal rates of the poisonous elements F, Cl, and As were 96.61%, 97.03%, and 96.86%, respectively. This shows that extending the calcination time in the first stage is beneficial to the removal of F, Cl, and As.

[0050] Example 9

[0051] Example 1 was repeated, except that the calcination time in S2 was 100 min, and the other conditions remained unchanged. The results showed that the removal rates of the poisonous elements F, Cl, and As were 98.12%, 98.33%, and 98.12%, respectively. This shows that further extending the calcination time in the first stage is not very meaningful in removing F, Cl, and As.

[0052] Example 10

[0053] Example 1 was repeated, except that the roasting temperature in S3 was 850°C, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 97.13% and 97.25%, respectively, indicating that increasing the second stage roasting temperature is beneficial to promoting the decomposition of calcium sulfate into calcium oxide, that is, promoting the occurrence of reaction (1) and reaction (2), thereby promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high silicon iron cobalt slag during the co-roasting process, thereby improving the leaching rate of iron and cobalt during the low-temperature acid leaching process.

[0054] Embodiment 11

[0055] Example 1 was repeated, except that the roasting temperature in S3 was 920°C, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 99.13% and 99.34%, respectively, indicating that further increasing the second stage roasting temperature had little effect on promoting the decomposition of calcium sulfate into calcium oxide, and thus had no significant effect on improving the leaching rates of iron and cobalt in the low-temperature acid leaching process.

[0056] Example 12

[0057] Example 1 was repeated, except that the roasting time in S3 was 70 min, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 97.13% and 97.34%, respectively, indicating that extending the second roasting time is beneficial to promoting the decomposition of calcium sulfate into calcium oxide, that is, promoting the occurrence of reaction (1) and reaction (2), thereby promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high-silicon iron-cobalt slag during the co-roasting process, thereby improving the leaching rates of iron and cobalt during the low-temperature acid leaching process.

[0058] Example 13

[0059] Example 1 was repeated, except that the roasting time in S3 was 100 min, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 99.14% and 99.36%, respectively, indicating that further extending the second roasting time had little effect on promoting the decomposition of calcium sulfate into calcium oxide.

[0060] Embodiment 14

[0061] Example 1 was repeated, except that the roasting temperature in S4 was 1050°C, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 97.14% and 97.38%, respectively, indicating that increasing the roasting temperature in the third stage was beneficial to promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high-silicon iron-cobalt slag during the co-roasting process, thereby improving the leaching rates of iron and cobalt during the low-temperature acid leaching process.

[0062] Embodiment 15

[0063] Example 1 was repeated, except that the calcination temperature in S4 was 1200°C, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the calcined product after low-temperature acid leaching were 99.13% and 99.35%, respectively, indicating that further increasing the calcination temperature in the third stage was of little significance in promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high-silicon iron-cobalt slag during the co-calcination process, and thus it was impossible to further improve the leaching rates of iron and cobalt during the low-temperature acid leaching process.

[0064] Example 16

[0065] Example 1 was repeated, except that the roasting time in S4 was 100 min, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 98.03% and 98.15%, respectively, indicating that extending the roasting time in the third stage was beneficial to promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high-silicon iron-cobalt slag during the co-roasting process, thereby continuing to improve the leaching rates of iron and cobalt during the low-temperature acid leaching process.

[0066] Embodiment 17

[0067] Example 1 was repeated, except that the roasting time in S4 was 130 min, and the other conditions remained unchanged. The results showed that the iron and cobalt leaching rates of the roasted product after low-temperature acid leaching were 99.14% and 99.35%, respectively, indicating that further extending the third roasting time had little effect on promoting the full decomposition of Fe2SiO4 and Co2SiO4 in the high-silicon iron-cobalt slag during the co-roasting process, and thus it was impossible to further improve the leaching rates of iron and cobalt during the low-temperature acid leaching process.

[0068] Embodiment 18

[0069] Example 1 was repeated, except that the leaching temperature in S5 was 50°C, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt of the roasted product after low-temperature acid leaching were 97.21% and 97.37%, respectively, indicating that increasing the leaching temperature is beneficial to improving the leaching rates of iron and cobalt.

[0070] Embodiment 19

[0071] Example 1 was repeated, except that the leaching temperature in S5 was 70°C, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt were 99.13% and 99.37% respectively after the roasted product was treated with low-temperature acid leaching, indicating that further increasing the leaching temperature was not very meaningful for improving the leaching rates of iron and cobalt.

[0072] Embodiment 20

[0073] Example 1 was repeated, except that the leaching time in S5 was 40 min, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt were 91.11% and 92.03% respectively after the roasted product was treated with low-temperature acid leaching, indicating that extending the leaching time is beneficial to improving the leaching rates of iron and cobalt.

[0074] Embodiment 21

[0075] Example 1 was repeated, except that the leaching time in S5 was 70 min, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt were 99.12% and 99.33% respectively after the roasted product was treated with low-temperature acid leaching, indicating that further extending the leaching time did not have much effect on improving the leaching rates of iron and cobalt.

[0076] Embodiment 22

[0077] Example 1 was repeated, except that the concentration of sulfuric acid in S5 was 0.3 mol / L, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt were 92.16% and 92.34% respectively after the roasted product was treated with low-temperature acid leaching, indicating that increasing the concentration of sulfuric acid was beneficial to improving the leaching rates of iron and cobalt.

[0078] Embodiment 23

[0079] Example 1 was repeated, except that the concentration of sulfuric acid in S5 was 0.5 mol / L, and the other conditions remained unchanged. The results showed that the leaching rates of iron and cobalt in the roasted product after low-temperature acid leaching were 99.14% and 99.36%, respectively, indicating that further increasing the concentration of sulfuric acid had little effect on improving the leaching rates of iron and cobalt.

Claims

1. A method for cleaning heavy metal gypsum slag, characterized in that: Heavy metal gypsum slag, high silicon iron cobalt slag and carbonaceous reducing agent are ground and mixed to obtain a mixed powder; the mixed powder is subjected to three-stage roasting in sequence, wherein the first stage roasting volatilizes and removes harmful components including F, Cl and As; the second stage roasting decomposes calcium sulfate and converts it into calcium oxide and sulfur dioxide; the third stage roasting realizes phase reconstruction of high silicon iron cobalt slag to obtain a roasting product including Fe2O3, Fe3O4, CoO, Co3O4 and CaSiO3; the roasting product is acid leached to obtain an iron-cobalt leaching solution.

2. The method for cleaning heavy metal gypsum slag according to claim 1, characterized in that: The mass ratio m of heavy metal gypsum slag to high silicon iron cobalt slag in the mixed powder (重金属石膏污泥) :m (高硅铁钴渣) =1~3.

3. The method for cleaning heavy metal gypsum slag according to claim 2, characterized in that: The mass content of CaSO4 in the heavy metal gypsum slag is 65-85%; The high silicon iron cobalt slag has a Fe2SiO4 content of 60-80wt% and a Co2SiO4 content of 10-15%.

4. The method for cleaning heavy metal gypsum slag according to claim 1, characterized in that: The amount of the carbonaceous reducing agent used is 5% to 20% of the mass of the heavy metal gypsum slag and the high silicon iron cobalt slag.

5. A method for cleaning heavy metal gypsum slag according to any one of claims 1 to 4, characterized in that: The conditions of the first stage calcination are: calcination under a protective atmosphere, calcination temperature of 500-800°C, calcination time of 30- 120min.

6. A method for cleaning heavy metal gypsum slag according to any one of claims 1 to 4, characterized in that: The conditions of the second stage roasting are: roasting in a protective atmosphere, a roasting temperature of 800-900° C., and a roasting time of 30 min-90 min.

7. A method for cleaning heavy metal gypsum slag according to any one of claims 1 to 4, characterized in that: The conditions of the three-stage calcination are: calcination under a protective atmosphere, a calcination temperature of 900 to 1200° C., and a calcination time of 30 to 180 minutes.

8. A method for cleaning heavy metal gypsum slag according to any one of claims 1 to 4, characterized in that: The acid leaching conditions are: leaching temperature of 45-65° C., leaching time of 30-60 min, and acid concentration of 0.2-0.5 mol / L.

9. The method for cleaning heavy metal gypsum slag according to claim 8, characterized in that: The acid is sulfuric acid.

Citation Information

Cited By

  • Method for removing impurity elements in high-purity quartz sand

    CN120172417A